O mo(vi)mento do discurso em Górgias: do tratado sobre a natureza ou não-ser para o elogio de Helena - Brazil, Vicente Thiago Freire (2012)
The aim of this research is central reason on the concept of discursiveness in Gorgias of Leontino based two of his main works in the accessible, The Treaty on the Non-being or About The Nature and Praise of Helena. Intend to demonstrate that the Logos has in Georgias a role of full mention, and this is a constant theme of "moment" in gorgian thought, which may be understood as the wire of the work of the leontineese. Despite the recognition of "moment" of the speech in Gorgias, it shows that also in this research that this is absolutely dynamic, alive, pure "movement". Starting with an analysis of the sociocultural context of sophistry - in which are presented and discussed the main issues surrounding the thinkers who are related in this movement - is followed by detailed discussion of both texts, with the assumption of reading for understanding the Treaty in the gorgian Meontology founding the "moment" of discourse in Western thought, and praise the omnipotence of the logos that puts the cultural reality in which human nature is "movement" for the tragedy of our existence is softened.